2013
DOI: 10.1007/s00264-013-1934-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of the retrocapital metatarsal percutaneous osteotomy for hallux valgus

Abstract: Purpose The current trend in hallux valgus surgery is directed toward percutaneous procedures. However, no evidence that any of these methods of treatment are superior to the others has been described, excepting studies in the long term. The aim of this study was to analyse a series of patients who had undergone a percutaneous distal retrocapital osteotomy of the first metatarsal, and had been followed up for ten years. Methods We carried out a clinical and radiological evaluation of 115 feet ten years after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 24 publications
9
32
0
Order By: Relevance
“…Overall, in 92.5% of our cases, there was improvement, which is comparable with that reported in the literature [10, 25, 35, 3844] (Figs. 5 and 6).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, in 92.5% of our cases, there was improvement, which is comparable with that reported in the literature [10, 25, 35, 3844] (Figs. 5 and 6).…”
Section: Discussionsupporting
confidence: 92%
“…In the sub-groups, the mean AOFAS score at the last follow-up was 87.1 points (Δ = +32.1) in the mild HV group, 86.6 (Δ = +32.7) in the moderate HV group and 83.7 (Δ = +30.2) in the severe one. Overall, the AOFAS score found in our study was comparable to those reported by different authors not only using minimally invasive techniques [10, 12, 13, 25, 26, 38], with or without osteosynthesis, but also with series of open surgical procedures using Chevron, Scarf or proximal metatarsal osteotomies [10, 13, 19, 39, 40]. In particular, our data was similar for patient demographic aspects and complications, including stiffness; however, our group of patients had a larger sample size and follow-up duration [10, 13, 19, 39].…”
Section: Discussionsupporting
confidence: 90%
“…It is a common experience that it is not possible to easily mobilise such wire after fixation. However, as indicated by our results and results of other authors reporting on a similar kind of fixation [3,6], nonunion and delayed union, as well as dorsal malunion, are extremely rare with this kind of fixation, as the dorsal translation is also limited by the sagittal oblique osteotomy line, which approximates 15°i n the dorsal to plantar and the distal to proximal direction, which improves the intrinsic stability of the construct. 4.…”
supporting
confidence: 66%
“…Therefore, in contrast from what occurs in open procedures, minimally invasive procedures are accompanied by a lateral soft tissue release only in carefully selected cases. Subcapital osteotomies, in particular, despite usually not being associated with lateral soft tissue release, allow repositioning of the metatarsal head and properly repositioning the sesamoids and are associated with good long-term results [3]. 2.…”
mentioning
confidence: 99%
“…In an attempt to compare our findings with the reports made by previous researchers, we found 14 retrospective studies outlining results of minimally invasive hallux valgus surgery. Most of them presented good clinical outcome in mid-term [ 12 , 23 ] as well as in long-term follow-up after ten years [ 24 ]. Radiological outcome also revealed good results [ 9 , 12 ].…”
Section: Discussionmentioning
confidence: 99%